Pendidikan Kesehatan dalam Meningkatkan Kepatuhan Merawat Kaki pada Pasien Diabetes Mellitus Tipe II - Nova Nur Windasari (Universitas Muhammadiyah Yogyakarta, 2015)
Background: Diabetes mellitus feet complications are a leading cause of mortality in developing countries. The prevalence of diabetes is expected to increase in the next decade in the developing countries. Foot care of patients with diabetes mellitus type II is consisted of early detection, foot exercise and practice for the foot care. The aim of this study was to determine the adherence of foot care after the education program was given to reduce of diabetic foot complications in the health center Mergangsan area in Yogyakarta. Method: This research used quasy experimental design with pre and post test group control. The total samples were 82 respondents (41 for the intervention group, 41 for the control group). Instrument used Nottingham Asessment of Functional Foot Care and Diabetic Foot Care Behaviour. Wilcoxon test results of intervention and control group in this research between pre and post intervention was p-value = 0.000 (p-value 0.05), that signifi cant diff erence of adherence for the practice of foot care. Mann-Whitney test result p-value 0,000 (p-value 0,05), which means there was a signifi cant diff erence in adherence between the intervention and control group. Health education can improve patient adherence foot care for diabetes mellitus type II in the area health center Mergangsan in Yogyakarta. Suggestion for further research is examining factors that infl uence adherence for the foot care practice with daily observations.Key words : Adherence, Foot care, Health Education